2023
DOI: 10.3390/app13063697
|View full text |Cite
|
Sign up to set email alerts
|

H∞ Optimization of a Novel Maxwell Dynamic Vibration Absorber with Lever, Inerter, and Grounded Stiffness

Abstract: In this paper, we propose a novel Maxwell dynamic vibration absorber (DVA) with lever, inerter, and grounded stiffness. Firstly, the governing equation of the coupled system is established. The analytical formula of the amplitude amplification factor of the primary system and the natural frequencies of the coupled system are derived. There are three fixed points in the amplitude–frequency response curve of the primary system, which are independent of damping. Then, based on H∞ optimization criterion, two possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The connection positions of spring elements and damping elements are also varied. In recent years, new components such as negative stiffness spring [10], amplification mechanism [11], and inerter device [12] have been deeply investigated in structural vibration suppression due to their excellent vibration control performance, which play an important role and bring the possibility for further improvement of DVA performance. In order to pursue better vibration reduction performance and higher cost performance under different actual needs, the collocation and combination of the whole system and the corresponding parameter optimization method have always been the research content of various scholars.…”
Section: Introductionmentioning
confidence: 99%
“…The connection positions of spring elements and damping elements are also varied. In recent years, new components such as negative stiffness spring [10], amplification mechanism [11], and inerter device [12] have been deeply investigated in structural vibration suppression due to their excellent vibration control performance, which play an important role and bring the possibility for further improvement of DVA performance. In order to pursue better vibration reduction performance and higher cost performance under different actual needs, the collocation and combination of the whole system and the corresponding parameter optimization method have always been the research content of various scholars.…”
Section: Introductionmentioning
confidence: 99%
“…As simple amplification mechanisms, levers were often used to amplify the displacement and force in the vibration control system and enhance the system's performance. Some scholars introduced levers into the inerter absorber to further optimize the structural design and vibration absorption performance of the absorber [27,28]. Liu et al [29] introduced linear and nonlinear inerters into locally resonant acoustic metamaterials and found that the structure based on the nonlinear inerter was insensitive to changes in the inerter's coefficient.…”
Section: Introductionmentioning
confidence: 99%